EMOTIONAL SPHERE OF ADOLESCENTS WHO EXPERIENCED DOMESTIC VIOLENCE - Razina, N. V.; Danshina, D. S. (Modern Psychology, 2019)
The article presents a comparative study of intensity of posttraumatic stress disorder symptoms among adolescents who experienced domestic voidance and those, who did not. In spite of the fact that intensity of post-traumatic stress disorder symptoms did not show significant difference, correlation relationship between emotional parameters of children who experienced violence and children who did not experience violence differed. It was also discovered that adolescents who experienced domestic violence express envy and hatred against people around, caused by bitterness and anger to the whole world for real or perceived suffering.